Genome Sequences of Livestock-Associated Methicillin-Resistant Staphylococcus aureus spa Type t899 Strains Belonging to Three Different Sequence Types (ST398, ST9, and ST4034) - Tegegne, Henok Ayalew (Microbiol Resour Announc, 2019)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) is an emerging MRSA lineage rapidly evolving in the community. In this report, we present the draft genome sequences of nine LA-MRSA strains. These strains were isolated from meat and a human nasal swab sample and belong to one unique spa type (t899), but to three different sequence types, ST398, ST9, and ST4034.